Some Practical Considerations in Developing Effective Compliance Programs: A Framework for Meeting the Requirements of the Sentencing Guidelines - Dan K. Webb; Steven F. Molo (Washington University Law Quarterly, 1993)
This Article discusses the advantages and disadvantages of implementing an effective compliance program. It then discusses the specific elements that the Guidelines require for a sentencing court to find a compliance program effective and thus entitled to credit as a mitigating factor in the sentencing process. Finally, the Article sets forth a basic framework for establishing a compliance program that will satisfy the Guidelines' requirements.
Keywords: Criminal liability of juristic persons; Sentencing guidelines (Criminal procedure)